Selective stimulation of catecholamine release from bovine adrenal chromaffin cells by an ionotropic purinergic receptor sensitive to 2-methylthio ATP - Tomé, Ângelo R. (2007)
Background 2-Methylthioadenosine 5'-triphosphate (2-MeSATP), formerly regarded as a specific P2Y (metabotropic) purinergic receptor agonist, stimulates Ca2+ influx and evokes catecholamine release from adrenal chromaffin cells. These cells express P2Y and P2X (ionotropic) purinoceptors, with the latter providing an important Ca2+ influx pathway. Using single cell calcium imaging techniques, we have determined whether 2-MeSATP might be a specific P2X receptor agonist in bovine chromaffin cells and assessed the relative role of P2X and P2Y receptors on catecholamine secretion from these cells. Results ATP raised the [Ca2+]i in ~50% of the cells. Removing extracellular Ca2+ suppressed the [Ca2+]i-raising ability of 2-MeSATP, observed in ~40% of the ATP-sensitive cells. This indicates that 2-MeSATP behaves as a specific ionotropic purinoceptor agonist in bovine chromaffin cells. The 2-MeSATP-induced [Ca2+]i-rises were suppressed by PPADS. UTP raised the [Ca2+]i in ~40% of the ATP-sensitive cells, indicating that these expressed Ca2+-mobilizing P2Y receptors. UTP-sensitive receptors may not be the only P2Y receptors present, as suggested by the observation that ~20% of the ATP-sensitive pool did not respond to either 2-MeSATP or UTP. The average sizes of the ATP- and 2-MeSATP-evoked [Ca2+]i responses were identical in UTP-insensitive cells. 2-MeSATP stimulated Ca2+ influx and evoked catecholamine release, whereas UTP elicited Ca2+ release from intracellular stores but did not evoke secretion. 2-MeSATP-induced secretion was strongly inhibited by Cd2+ and suppressed by extracellular Ca2+ or Na+ removal. TTX inhibited 2-MeSATP-evoked secretion by ~20%. Conclusion 2-MeSATP is a specific P2X purinoceptor agonist and a potent secretagogue in bovine chromaffin cells. Activation of 2-MeSATP-sensitive receptors stimulates Ca2+ influx mainly via voltage-sensitive Ca2+ channels. For the most part, these are activated by the depolarization brought about by Na+ influx across P2X receptor pores